STRATEGI PENYELENGGARAAN DIKLAT DAN UJIAN SERTIFIKASI KEAHLIAN PENGADAAN BARANG/ JASA PEMERINTAH DI LINGKUNGAN PEMERINTAH KABUPATEN MAGELANG - Wiharyanto Wiharyanto (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
The study aims to analyze about the low graduation and certification exam training participants of the procurement of goods / services of the government and its contributing factors, and formulate a strategy of education and training and skills certification exams procurement of goods / services of the government. Collecting data using the method of study documentation, interviews, and questionnaires. Is the official source of information on the structural and functional Regional Employment Board, as well as the participants of the training and skills certification exams procurement of goods / services of the government in Magelang regency government environment. Analysis using 4 quadrant SWOT analysis, to determine the issue or strategic factors in improving the quality of education and training and skills certification exams procurement of government goods / services within the Government of Magelang regency. The results show organizer position is in quadrant I, which is supporting the growth strategy, with 3 alternative formulation strategies that improve the quality of education and training and skills certification exams procurement of government goods / services, and conducts certification examination of the procurement of government goods / services with computer assisted test system (CAT). Based on the research recommendations formulated advice to the organizing committee, namely: of prospective participants of the training and skills certification exams procurement of goods / services the government should consider the motivation of civil servants, is examinees who have attended training in the same period of the year, the need for simulation procurement of goods / services significantly, an additional allocation of training time, giving sanction to civil servants who have not passed the exam, the provision of adequate classroom space with the number of participants of each class are proportional, as well as explore the evaluation of education and training and skills certification exams procurement of goods / services for Government of participants.